EVALUATION OF NEW OIL PALM CROSSES’ FOR THEIR FRESH FRUIT BUNCH YIELD IN ANDHRA PRADESH - P. MADHAVI LATHA*, M. THIRUPATHI REDDY, G. RANGANNA, B. PRATAP, G. RAVICHANDRAN; B. AUGUSTINE JERARD (The Journal of Research ANGRAU, 2024)
India is one of the world’s major vegetable oil importers and second largest consumer. There is scope to raise the productivity of oil palm to two folds with the current land use and with the development of new hybrids. In this regard, 10 new oil crosses (D x P) were evaluated for 12 years (2011 to 2023) at Horticultural Research Station, Vijayarai, Andhra Pradesh. The number of bunches produced per palm per year has risen from 4 to 6 years after planting and decreased from 7 to 10 YAP, where these crosses recorded an average bunch weight of 2 kg to 3 kg in the first harvest year, while it was 20 kg to 24 kg, by palms reaching 11 to 12 years after planting (8th and 9th harvest years). Out of all the nine production years (4 YAP to 12 YAP), NRCOP-37 produced the highest number of bunches in five production years and in the remaining four years also it recorded on par bunch production with high yielding cross of that particular year. In the yield stabilization period (9 to 12 YAP), NRCOP-37 recorded the highest yield of 200 kg (9 YAP), 203.97 kg (10 YAP), and 206.09 (12 YAP) kg/palm/year in the above three harvesting years. While the cross NRCOP-39 recorded 263.73 kg/palm/year of FFB at 11 years after planting. The cross NRCOP-37 recorded a higher FFB yield of 28.61 t/ha/year by the 6th harvest year (9 YAP) and this cross recorded FFB yields of 29.16, 34.37, and 29.47 t/ha/year at the 7th, 8th and 9th harvest years. This is the one cross where annual yield fluctuation (FFB production).